DAKWAH DAN PERUBAHAN SOSIAL: STUDI TERHADAP PERAN MANUSIA SEBAGAI KHALIFAH DI MUKA BUMI - Abu Bakar Madani (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Abstract Da’wa is a process of increasing the quality of faith within human soul according to the Islamic sharia. This process is continuous, systematic and it should be carried out step by step. This process aims at activating the act of continuous improvement within oneself. Enhancing faith towards god is manifested in the form of enhancing knowledge, awareness, and good deeds. Therefore, it is a moral obligation for Muslims to keep the course of social change on track through introducing and implementating Islamic values in every aspect of life. Thus, it is not an exaggeration to say that achieving the goal of divine social change according to Islam can onle be carried out by da’wa activity.